Chronic Diarrhea in Dogs – Retrospective Study in 136 Cases. (July 2017) - Volkmann, M.; Steiner, J.M.; Fosgate, G.T.; Zentek, J.; Hartmann, S.; Kohn, B.
Abstract : Background: Chronic diarrhea (CD) is common in dogs, and information on frequency and distribution of primary and secondary causes is lacking. Objectives: To evaluate underlying causes and predictors of outcome in dogs with CD. Animals: One hundred and thirty‐six client‐owned dogs with CD (≥3 weeks duration). Methods: Retrospective review of medical records (Small Animal Clinic, Freie Universität Berlin, Germany, 09/2009‐07/2011). Quantification of final diagnoses and comparison of clinical aspects including disease severity and clinicopathological abnormalities among dogs with clinical remission (either complete [gastrointestinal signs absent] or partial [clinical improvement of gastrointestinal signs and reduced episodes with shortened duration]), and those without recovery. Results: Ninety percent of dogs were diagnosed with a primary enteropathy: inflammatory (71%; of those 66% dietary responsive, 23% idiopathic, 11% antibiotic responsive), infectious (13%), neoplastic (4%), and in one dog each mechanical disease or systemic vasculitis. Secondary causes were diagnosed in 10% of dogs: exocrine pancreatic (6%), endocrine (2%), and in one dog each hepatic, renal, and cardiac disease. In total, 87% of dogs had clinical remission, whereas 13% died or did not respond to treatment: Lack of recovery was frequently recorded for dogs with primary inflammatory (idiopathic) or neoplastic disease and was significantly associated with increased disease severity scores ( P = .005), anemia (hematocrit < 40%, P < .001), severe hypoalbuminemia (serum albumin <2.0 g/dL, P = .008), and severe hypocobalaminemia (serum cobalamin concentration <200 pg/mL, P = .006). Conclusions and clinical importance: Inflammatory enteropathies and particularly those of dietary origin were the most common causes of CD in dogs. Findings support the usefulness of hematocrit, and serum albumin and cobalamin concentration as prognostic markers in dogs with CD.